The curative bloom : an investigation of medicinal botanical imagery incorporating precious metals and enamel as body adornment - Friedland, Mara (East Carolina University, 2009)
This written report supports the creative thesis entitled The Curative Bloom. The historical exploration of the medicinal uses of plant life, along with a technical investigation of casting, forming and enameling processes, cumulates in a creative body of jewelry work focusing on healing herbs and their correlation to the body.
Keywords: Fine arts; Biology, Botany; Botanical; Herbalism; Jewelry; Metals; Botany; Decoration and ornament--Plant forms; Jewelry making--Themes, motives; Plants--Symbolic aspects; Medicinal plants in art; Enamel and enameling